The effect of tamoxifen on the endometrium, serum lipids and hypothalamus pituitary axis in the postmenopausal breast cancer patients - (:unkn) unknown (WILEY, 2000)
Background. There is still no cost-effective endometrial screening method for asymptomatic postmenopausal breast cancer patients using tamoxifen. We investigated the effectivity of transvaginal ultrasonography and endometrial sampling as a screening method for asymptomatic patients. Additionally the effect of tamoxifen on hypothalamus-pituitary axis and serum lipid profiles were investigated. Methods. Sixty-seven gynecologically asymptomatic postmenopausal breast cancer patients were enrolled in this randomized crossover study. Endometrial thickness was determined by transvaginal ultrasonography, endometrial biopsy was obtained by Pipelle or fractional curettage hormone and lipid profiles were compared in the two groups which consisted of forty-seven tamoxifen user (cases) and twenty nonuser (controls) patients. Results. The mean endometrial thickness measured by transvaginal sonography was 7.8 mm (3-20 mm) versus 3.7 mm respectively. The difference was significant in tamoxifen users. The most common histopathologic finding was endometrial polyp, detected in five patients. In the control group then was no endometrial polyp. The positive histopathologic findings were present in twenty-two patients in the case group but there were only two patients with positive histopathologic findings in the control group. Ultrasound findings did not correlate with the presence of endometrial abnormalities on biopsy and no endometrial cancer or hyperplasia were detected. In tamoxifen users serum FSH and LH levels were significantly lower than in nonusers. Serum HDL levels were significantly higher in the case group. Conclusion. Ultrasonographic imaging of the endometrium in asymptomatic postmenopausal breast cancer patients using tamoxifen should be interpreted with caution. Other imaging techniques should be used for more specific information about the endometrium.
Keywords: breast cancer; endometrium; tamoxifen; ADJUVANT TAMOXIFEN; WOMEN; TRIAL